Education for All within Emerging Context: Ivorian Experience, Issues and Perspectives - Oyeniran, Rassidy; Mcjerry, Bekoe A. (American Journal of Social Sciences and Humanities, 2019)
It is the sole aim of every country to ensure that Education for All (EFA) becomes a reality. The presence of educational challenges that pose a threat to the attainment of EFA are worrisome. The obstacles to educational development in a changing environment such as Cote d’Ivoire are being eradicated gradually by sound measures. However, there exist some challenges that call for immediate policy reassessment and re-evaluation as well as prompt actions on the part of the government and key stakeholders. These seeming challenges called for this study. This paper sought to unveil some of the challenges and as well propose workable recommendation. The study employed a qualitative approach to analyze its outcomes by conducting document analysis. The results showed that despite sustained efforts since 2012, there are some traits of failures in the system. These include low enrolment at the secondary level, discrimination against the girl-child, variance in the school curriculum and the demands on the job market, to mention but a few. This paper recommended among other to things to policymakers and stakeholders in the education sector of Cote d’Ivoire the need to further establish and develop an inclusive approach to compulsory schooling for children from 6 to 16 years. It is suggested that reforms should be carefully enacted, and additional resources are to be planned through the National Development Plan.